1977
DOI: 10.1017/s0022172400053109
|View full text |Cite
|
Sign up to set email alerts
|

Possible spread of African horse sickness on the wind

Abstract: SUMMARYAnalyses of outbreaks of African horse sickness showed that movement of infected Culicoides midges on the wind was most likely responsible for the spread of the disease over the sea from Morocco to Spain in 1966, from Turkey to Cyprus in 1960, and from Senegal to the Cape Verde Islands in 1943. The pattern of spread of the epidemic in the Middle East in 1960 could have been laid down by the infected midges carried on spells of south-east winds, and analyses of outbreaks in Algeria in 1965 and India in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(51 citation statements)
references
References 21 publications
1
50
0
Order By: Relevance
“…Before it was known even that BEFV is transmitted by Culicoides, Seddon (155) demonstrated that the spread of BEF in Australia was explainable by wind patterns. Subsequently, numerous studies have related the spread of Culicoides-borne viral diseases to wind movements (25, 28, 50, 66,115,124,127,137,158,159,160,162,163,164). In all cases the evidence is circumstantial, and alternative modes of introduction can rarely be ruled out.…”
Section: Dispersalmentioning
confidence: 99%
“…Before it was known even that BEFV is transmitted by Culicoides, Seddon (155) demonstrated that the spread of BEF in Australia was explainable by wind patterns. Subsequently, numerous studies have related the spread of Culicoides-borne viral diseases to wind movements (25, 28, 50, 66,115,124,127,137,158,159,160,162,163,164). In all cases the evidence is circumstantial, and alternative modes of introduction can rarely be ruled out.…”
Section: Dispersalmentioning
confidence: 99%
“…However, at intervals the virus makes excursions beyond these enzootic zones to initiate epizootics ranging as far as India and Pakistan in the East [1], Turkey and Cyprus in the North [1,2] and Morocco and the Cape Verde Isles in the West [2]. The first recorded outbreak of AHS in Spain occurred in early October 1966 during an epizootic of type 9 AHSV which was centred in North Africa [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Capable of wind-borne displacement for several hundred kilometers, Culicoides spp. have a capacity for rapid long-distance transmission of disease and have recently been responsible for the establishment of enzootic BTV and SBV infections over vast new geographic areas (1,2). Current control methods for Culicoides include breeding site removal and baiting of livestock and midge resting sites; however, these techniques are costly and labor-intensive and have various levels of success and permanence of control (3).…”
mentioning
confidence: 99%